The impact of several demographic factors on chemistry laboratory anxiety and self-efficacy in students' first year of university. - Rummey, Cara; Clemons, Tristan D.; Spagnoli, Dino (Student Success v.10 n.1 p.87-98 https://doi.org/10.5204/ssj.v10i1.1104, 2019)
The transition from high school to tertiary education can be a daunting prospect for students. The prospect of laboratories, an unfamiliar environment, for students, can increase levels of anxiety. Moreover, there is a growing body of evidence that suggests that students' self-efficacy is inversely correlated with students' anxiety. We surveyed students at the start and end of a semester to evaluate levels of anxiety and self-efficacy in relation to several aspects of the chemistry laboratory. Time management and answering assessed questions are the aspects that contribute to high levels of anxiety and low levels of self-efficacy at the start of semester. Students generally reported lower anxiety and higher self-efficacy at the end of the semester about every aspect probed. These results are of interest to any discipline that offers an unfamiliar learning environment for students as aspects such as time management and answering assessed questions are not discipline specific. We investigated the different aspects of anxiety and self-efficacy in relation to various demographic factors. [Author abstract]